A Brief Discussion on the Management of enterprise Current Funds - Han, Dong; Cong, Lin Lin (Journal of Theory and Practice of Social Science, 2023)
With the development of society, enterprises are facing more and more financial risks, and the amount of funds between enterprises has increased significantly. However, some enterprises have not paid much attention to the management of funds, and have not cleaned up the funds regularly, resulting in overdue and abnormal payment of funds, which brings certain financial risks to enterprises. This paper, based on the current situation of enterprise current fund management, mainly puts forward some measures to strengthen the liquidation of enterprise current fund, hoping to standardize the management of enterprise current fund and reduce financial risks.